2017
DOI: 10.1002/cncr.31061
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk associated with atypical hyperplasia and lobular carcinoma in situ initially diagnosed on core‐needle biopsy

Abstract: In patients who had an initial diagnosis of atypical hyperplasia or lobular carcinoma in situ on core biopsy, the 7-year cumulative breast cancer incidence was 9.9%. Most tumors were ipsilateral, stage I, estrogen receptor-positive, invasive carcinomas. The current data support close clinical and radiologic follow-up for more than 5 years in this patient population. Cancer 2018;124:459-65. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 39 publications
2
15
0
2
Order By: Relevance
“…Carcinoma of the breast can arise from either the lobular or the ductal epithelium. Lobular carcinomas are less prevalent than ductal, accounting for 4–10% of diagnoses from breast biopsies [1]. Before BCa reaches the invasive stage at which point it can spread to the rest of the body, it is referred to as a pre-invasive lesion (Figure 1).…”
Section: Lesions Of the Breastmentioning
confidence: 99%
“…Carcinoma of the breast can arise from either the lobular or the ductal epithelium. Lobular carcinomas are less prevalent than ductal, accounting for 4–10% of diagnoses from breast biopsies [1]. Before BCa reaches the invasive stage at which point it can spread to the rest of the body, it is referred to as a pre-invasive lesion (Figure 1).…”
Section: Lesions Of the Breastmentioning
confidence: 99%
“…Our study showed that 18.36% of intraductal papillomas coexist with malignancy, and 37.33% coexist with ADH, ALH or LCIS. The rate of coexistence with AH or LCIS is obviously higher than the rate previously indicated in Table 2 Evidence supporting the excision of papilloma with AH is certainly incontrovertible [21,22] . The treatment of intraductal papilloma without atypia is controversial and presents the notion, to observe or to excise?…”
Section: Discussionmentioning
confidence: 70%
“…After an average follow-up of 38 months, we found that 3 in 5 patients presented no lesions, and no enlargement process was found in the other 2 patients' lesions. Donaldson et al [21] found that the 7-year cumulative breast cancer incidence rate was only 10% in patients who had an initial diagnosis of AHP on CNB, so they believed that close imaging follow-up was applicable to these patients. Furthermore, breast papillary carcinoma is rare, representing only 1-2% of all breast malignancies [22].…”
Section: Discussionmentioning
confidence: 99%